2013
DOI: 10.1007/s00774-013-0490-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risedronate alone or combined with vitamin K2 on serum undercarboxylated osteocalcin and osteocalcin levels in postmenopausal osteoporosis

Abstract: Risedronate decreases osteoporotic fracture incidence; however, its effects remain unclear in elderly osteoporotic patients. Vitamin K mediates carboxylation of osteocalcin (OC), and high undercarboxylated osteocalcin (ucOC) levels indicate vitamin K deficiency and increased osteoporotic fracture risk. We aimed to evaluate the effects of risedronate alone or combined with vitamin K2 on serum ucOC, OC, and incidence of vertebral fractures in elderly osteoporotic patients. A total of 101 women with postmenopausa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The fraction of imperfect γ-carboxylation is referred to as ucOC, which is produced and released from osteoblasts into the vitamin K insufficiency or deficiency. Serum ucOC is rapidly decreased with Vitamin K 2 treatment [10] . On the other hand, regular intake of vitamin K increases BMD, and reduces the bone fracture risk [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of imperfect γ-carboxylation is referred to as ucOC, which is produced and released from osteoblasts into the vitamin K insufficiency or deficiency. Serum ucOC is rapidly decreased with Vitamin K 2 treatment [10] . On the other hand, regular intake of vitamin K increases BMD, and reduces the bone fracture risk [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high level of serum ucOC induced by long-term warfarin therapy is considered one of the risks of osteoporosis. It has been reported that 4.5 ng/mL of ucOC has a cut-off value to determine vitamin K insufficiency or deficiency for osteoporotic fractures [10] . In addition, it was also reported that serum ucOC is an independent determinant of carotid artery calcification and negatively correlates with renal function [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Uncarboxylated osteocalcin (GluOC) constitutes ϳ10% of total circulating osteocalcin in adult mice under normal physiological conditions (2, 10). However, the serum concentration of GluOC is increased in pathological conditions such as vitamin K deficiency and osteoporosis (2,26,31). Animal studies have shown that an increase in the circulating concentration of GluOC prevents obesity and glucose intolerance (10,13,28,30).…”
mentioning
confidence: 99%
“…A smaller study [40] in 101 women comparing risedronate and K2 bitherapy versus monotherapy with risedronate failed again to demonstrate a reduction in vertebral fracture incidence between the two groups but found that ucOC levels were greater in patients with vertebral fractures treated with risedronate alone, in comparison with bitherapy. Finally, a small study [41] involving 62 postmenopausal women with rheumatoid arthritis and osteopenia or osteoporosis found that combined therapy with alendronate and vitamin K2, decreases ucOC and bone metabolism markers and increases BMD in both lumbar spine and femoral neck.…”
Section: Effect Of Vitamin K Supplements In Association With Othermentioning
confidence: 95%